2016
DOI: 10.1111/nuf.12191
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Homeless: Civil and Uncivil Interactions with Nurses, Self-Care Behaviors, and Barriers to Care

Abstract: Our findings indicate people who are homeless often perceive nurses to be uncivil and uncaring toward them; furthermore, our participants provide a unique description of healthcare interactions from the perspective of the homeless. These findings can be used as a basis for the development of education interventions for students and practicing nurses to assist them in learning to provide civil and compassionate care for the homeless.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…; Woith et al. ). However, men's comments and the large number of repeat attendees at the clinic suggest that barriers are being overcome and this service is accessible with approachable nurses who are addressing the breadth of needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Woith et al. ). However, men's comments and the large number of repeat attendees at the clinic suggest that barriers are being overcome and this service is accessible with approachable nurses who are addressing the breadth of needs.…”
Section: Discussionmentioning
confidence: 99%
“…These rely on a wide‐ranging skill set and strong interpersonal skills (Dawson & Jackson ; Woith et al. ).…”
Section: Homelessness and Healthmentioning
confidence: 99%
“…They described feeling judged and shamed and believed that nurses thought they were seeking drugs or that their illnesses and injuries were a result of their irresponsible behavior. Participants said they were reluctant to seek formal healthcare based on their prior negative experiences and that in the future they would do so only as a last resort . They asserted that nurses who do not fully understand their plight are less likely to really help them and meet their health care needs …”
Section: Review Of the Literaturementioning
confidence: 99%
“…While much of the literature addresses implicit bias toward ethnic and racial minorities, health care professionals also exhibit bias toward those who live in poverty and homelessness . Woith et al . reported that homeless patients perceived nurses to be less attentive, compassionate, and respectful, and more judgmental toward them than toward those patients with financial means.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Homeless individuals face many barriers to health and healthcare access. Among them is lack of trust, often reinforced through biases held by members of the healthcare profession, including nurses . Interactions with the homeless during nursing education are most often limited to provision of care in a clinic or hospital.…”
Section: Introductionmentioning
confidence: 99%